The Designing Garuda Indonesia Travel Fair Event Poster At Garuda Indonesia Booth Using Maluku Kakehan Motifs - Ikbal Sanusi Warwefubun; Ixsora Gupita Cinantya (Green Publisher Indonesia, 2024)
Indonesian tourism is a key driver of the national economy, with the potential to spur significant economic growth. The Indonesian Ministry of Tourism is committed to enhancing both the quantity and quality of tourism through various initiatives. Collaborative efforts between the government, industry, and community groups are exemplified in events like the Travel and Holiday Fair Jakarta, Indonesia Tourism Creative Economic Fair Jakarta, and Garuda Indonesia Travel Fair (GATF). These travel fairs are becoming essential sales promotion strategies for the Indonesian tourism industry, helping to introduce new products and stimulate public interest.One such initiative, the Garuda Indonesia Travel Fair, also plays a vital role in promoting the rich cultural heritage of Maluku by featuring the Kakehan Motif, a stylized sun ornament symbol from the Alifuru tribe on Seram Island. This study, using descriptive qualitative methods, explores the design of a booth exhibition that incorporates the Kakehan Motif to showcase and celebrate Maluku’s culture. The booth not only serves as a promotional platform for Maluku Province at the Garuda Indonesia Travel Fair but also acts as a communication medium, offering visitors an immersive experience. It provides a practical space for the creative expression of ideas and serves as a promotional tool for companies, institutions, and organizations. Through this visual media, the booth aims to elevate the Kakehan Motif's prominence, contributing to the broader efforts of cultural preservation and tourism promotion in Indonesia.